Honey fusion - Abdul Karim, Muhammad Shahrim; Abdul Halim, Nurhasmilaalisa; Mohamed Aris, Mohamed Haidrin; Abu Bakar, Ainul Zakiah (Universiti Putra Malaysia Press, 2013)
No other insect has served the needs of humankind like the honey bees. Even in religious, holy and noble references such as the Koran, Torah, Bible and Talmud, the miracles of honey have been cited several times. For centuries, honey is not only used as food but also as medicine wherein it helps prevent infection, fights bacteria, and promotes healing (wounds, burns, pains). During the ancient Egyptian era, honey is utilized for embalming and preserving mummies by preventing bacteria from reachingthe dead body. The role of honey is recognized in man's world of culinary. The best way to consume honey is to take it as it is because honey can be very soothing.